Effect Of Waste Gypsum From Ceramic Slip Casting Mould On The Properties Of Portland Cement [TN946. C514 2007 f rb]. - Chandara, Chea (2007)

(untitled)
The aim of this work is to investigate the possibility of using waste gypsum (CaSO4.2H2O) which is the waste material from the hydration of plaster of Paris in ceramic factory as a replacement or alternative material to natural gypsum (CaSO4.2H2O) in cement production.